2011
DOI: 10.1007/s10450-010-9319-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of oxygen-containing aromatics used in petrochemical, pharmaceutical and food industries by means of lignin based active carbons

Abstract: The adsorption processes of three aromatic chemicals onto activated carbons (ACs) from aqueous solutions have been studied. Eucalyptus kraft lignin obtained from cellulose industry as a residual biomass has been used to prepare activated carbons by physical activation with CO 2 . The influences of the activation time on the surface areas and pore volumes of the ACs were analyzed. The physicochemical properties and the surface chemical structure of the adsorbents have been studied by means of N 2 and CO 2 adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Table 4 shows the adsorption behavior, represented in the maximum adsorptive density ( q max⁡ ) and the Langmuir constant ( b ), of various adsorbents. For acetaminophen, the results were in agreement with those reported by others [ 27 , 28 ]. For diclofenac, GAC exhibited favorable adsorption characteristics in both affinity and capacity compared to chitosan or organo-zeolites [ 29 31 ].…”
Section: Resultssupporting
confidence: 93%
“…Table 4 shows the adsorption behavior, represented in the maximum adsorptive density ( q max⁡ ) and the Langmuir constant ( b ), of various adsorbents. For acetaminophen, the results were in agreement with those reported by others [ 27 , 28 ]. For diclofenac, GAC exhibited favorable adsorption characteristics in both affinity and capacity compared to chitosan or organo-zeolites [ 29 31 ].…”
Section: Resultssupporting
confidence: 93%
“…PA adsorption on AC, AC-T, and AC-G has been studied in order to evaluate the effect of the adsorbent physico-chemical properties (See Table 1). The effect of pH ranging from 2 to 10 on the PA adsorption on several activated carbons was evaluated in a previous work, where we found it to be negligible (Cotoruelo et al, 2011), for what adsorption experiments herein reported have been performed at neutral pH. Figure 6 shows the PA adsorption equilibrium isotherms at 25 • C. From these isotherms, it could be concluded the high ability of these carbon adsorbents to remove PA at very low equilibrium concentrations, obtaining large adsorption capacities even at 2 mg L −1 .…”
Section: Effect Of Textural Properties and Surface Chemistry On Paracmentioning
confidence: 99%
“…Our research team have lots of experience in the preparation of activated carbons from olive stone García-Mateos et al, 2015), hemp fiber ), lignin (Rodríguez-Mirasol et al, 1993;Gonzalez-Serrano et al, 1997, 2004Cotoruelo et al, 2009Cotoruelo et al, , 2011 or others biomass waste such as eucalyptus wood (Tancredi et al, 1996), Pinus caribaea sawdust (Márquez-Montesinos et al, 2001) or fruit skin (Marquez-Montesinos et al, 2002;Rosas et al, 2010). We have reported the effects of the activation process with chemicals and physical methods in the porosity and surface chemistry and how they improve the carbon adsorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…Phenols are introduced into surface water from industrial effluents such as those from the coal tar, gasoline, plastic, rubber proofing, disinfectants, the pharmaceutical and steel industries, domestic wastewater, agricultural run-off and chemical spills. Various methods have been proposed for the treatment of wastewaters containing pharmaceutical compounds [6]; one of these is adsorption on porous materials [7].…”
Section: Introductionmentioning
confidence: 99%